The Innovative Business Model Concept Generation for PT. LEN Industri Business Model Solutions in Achieving the Expected Net Profit Margin - Mappangara, Darman; Aldianto, Leo (The Indonesian Journal of Business Administration, 2012)
As a state owned company, PT. Len Industri(Persero), an electronic industry and infrastructure company,has passed three transformation phases throughout its effort inimproving the company performance in the passed 20 years. Inthe final state of the third transformation phase, despite itssignificant sales growth (averaging to 30 percent per year from2006), PT. Len is unable to achieve the expected KPI (keyperformance Indicator) for NPM (net profit margin) of 5% set bythe stake holder.In order to achieve the requested NPM, PT. Len has to carefullyselect projects with low COGS only (80% to 85%). This can onlybe done through a high value project content which means usingan innovative product that has a high selling value or bydeveloping an innovative business model which can givesignificantly higher return. In this case study, the latter choice ischosen.Business model initiative is not new to PT. Len, but acomprehensive way of creating the business model that involvesdetails steps has never been generated. Business ModelGeneration using a 9 blocks building concept is introduced here.The designing concept uses the â€œUnbundlingâ€ business modelpattern that suit business at PT. Len. The designing take exampleone of the business lines in the integrated PV (photovoltaic)system supply. This business is then recast into the standardizedformat of business model canvas and unbundled to get a new corebusiness. This new core business will improve the NPM of PT.Len Industri.Keywords: NPM, Business Model, COGS, KPI , Unbundling businesspattern